German school, French school, Italian school at the beginning of the Sprachwissenschaft (Atti del Sodalizio Glottologico Milanese, 2021)
German school, French school, Italian school at the beginning of the Sprachwissenschaft. The developments of the Schools of Linguistics in the 1800s are not easy to trace; this depends first of all on how the scientific debate, which at the time was essentially interdisciplinary, was conducted, i.e. in a variety of different places: in journals that were not necessarily specialized, in exchanges of letters, around issues related to professorships and academic posts. Still in the mid-twentieth century there were not many institutional places of scientific debate. Looking at this process in a finer perspective, observing the multiple places of debate at its beginnings, one can observe how the “fabric” of nineteenth-century linguistics, so rich and jagged, shows not only the traces of typically national linguistic reflections, but also of supranational interweaving processes that are the expression of a particular scientific or cultural cohesion among the scholars.